(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2012)
SEM observations of sculpture of spore wall of the genus of Riccia enabled new appraisal of old Riccia herbarium samples. Riccia beyrichiana, R. cavernosa, R. crinita, R. erinacea are new to Ukraine. On the other hand, Riccia ciliata and R. crystallina previously reported from Ukraine, have not been confirmed. New distribution data for Riccia bifurca and R. glauca are also provided.